A cidadania nacional no contexto das migrações internacionais - Ferreira Santos, Valdirene (Comparative Cultural Studies: European and Latin American Perspectives, 2018)
This work analyzes national citizenship, in some aspects of its development and transformations, from the emergence of the nation state to the present day, problematizing it in relation to international migrations as a reality that becomes increasingly present in different societies. From a sociological theoretical approach centered on the relations of inclusion and exclusion in Western societies, which become continually more pluralistic and globalized, he argues that despite the tendency towards universal universalization of modern citizenship, by gradually reaching the minority groups of different societies, this democratic institution, in its link with nationality, has in many ways allowed the marginalization and exclusion of foreigners and immigrants. In this sense, it discusses the limits of the citizen institution facing the international migrations of the globalized world for inclusion in globalized and plural societies. It concludes that other forms of citizenship that are more inclusive and disaggregated from the territory-nation-state nucleus begin to be visible, but the centrality of national citizenship continues to deepen the exclusion of immigrants and foreigners in the social space.